2021
DOI: 10.3389/fpubh.2020.589372
|View full text |Cite
|
Sign up to set email alerts
|

How Does Public Knowledge, Attitudes, and Behaviors Correlate in Relation to COVID-19? A Community-Based Cross-Sectional Study in Nepal

Abstract: Background: The COVID-19 pandemic has created a global health emergency requiring an effective public health response including citizen's roles in preventing spread and controlling the pandemic. Little is known about public knowledge, beliefs and behaviors in-relation to the pandemic in Nepal. This study aims to assess knowledge, attitude and practices (KAP) toward COVID-19 among the general public and to identify associated factors.Methods: A cross-sectional survey was conducted between May–June 2020 with a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 16 publications
11
16
0
1
Order By: Relevance
“…Taxi drivers with an educational level of secondary (grades 9-12) or above were 7.55 times more likely to have good knowledge than individuals with primary education only. This result was supported by previous studies in Northwest Ethiopia [57,58], in Egypt [59,60], in Pakistan [50,61], in Syria [39], in South Korea [62], in Nepal [63,64], in Iran [54] and in…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Taxi drivers with an educational level of secondary (grades 9-12) or above were 7.55 times more likely to have good knowledge than individuals with primary education only. This result was supported by previous studies in Northwest Ethiopia [57,58], in Egypt [59,60], in Pakistan [50,61], in Syria [39], in South Korea [62], in Nepal [63,64], in Iran [54] and in…”
Section: Discussionsupporting
confidence: 88%
“…Taxi drivers who had a positive attitude were more likely to have good knowledge than those with a negative attitude. This was supported by previous studies in Nigeria [46], Pakistan [61], China [66], Bangladesh [56,67], Iran [54] and in Nepal [63]. On the other hand, drivers' place of residence showed significant association with knowledge about COVID-19.…”
Section: Plos Onesupporting
confidence: 77%
“…Indeed, there are mixed findings regarding the knowledge on COVID-19 related to gender differences. Contradict to previous study which demonstrated higher knowledge on COVID-19 among females 13,23,31,32 , several other studies indicated that male possessed greater COVID-19 knowledge 17,24,26 .…”
Section: Asmentioning
confidence: 64%
“…knowledge, attitude and practice, collectively, plays a pivotal role in ensuring these efforts and managing the disease transmission, thereby, several research involving COVID-19 related KAP has been recently carried out to utilize the valuable information for a greater good of the community. The research on knowledge, attitude and practice regarding COVID-19 has expanded to many countries including Malaysia 11,12,13 , Singapore 14 , Bangladesh 15,16 , China, India, and Pakistan 17 , Egypt 18 , Hong Kong 19 , Iran 20 , Palestine 21 , South Korea 22 , Sudan 23 , and Uganda 24 , Syria 25 , Nepal 26 , and Northeast Ethiopia 27 , as an effort towards improving the communication and intervention in response to the pandemic 10 .…”
Section: Asmentioning
confidence: 99%
See 1 more Smart Citation